An impact of the first and second-largest shareholders on a catering effect: evidence from Poland - Pieloch-Babiarz, Aleksandra (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Dividend pay-out is a frequently undertaken research issue. However, there is no study on the impact of concentrated ownership on adjustment of dividend amount to investor sentiment for pay-outs. The paper contribute to the literature by filling the research gap regarding the catering effect in the context of principal-principal agency conflict and type II agency costs, monitoring hypothesis and expropriation hypothesis. Aim: The aim of the article is to investigate an impact of the first and second-largest shareholders on an adjustment of dividend pay-outs to investor sentiment for dividends. To achieve the aim, two hypotheses have been formulated, i.e. H1: if the first-largest shareholder is a strategic investor, a catering effect weakens; H2: an existence of significant second-largest shareholder moderates the extent to which companies cater to investor sentiment for dividends. Results: There are three main finding: 1) the number of shares held by the first-largest shareholder is lower in dividend payers, while the number of shares held by the second-largest shareholder is lower in dividend non-payers; 2) listed companies from electromechanical industry sector cater to investor sentiment for dividends; 3) both research hypotheses have not been satisfied.